Eksplorasi Strategi yang Efektif dalam Meningkatkan Kemampuan Komunikasi Matematis Siswa - Iwan Sasmita; Cucu Suryani (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
In learning mathematics, one of the abilities that must be possessed by students is the ability of students to communicate mathematically so that students can play an active role in the learning process. The purpose of this study was to explore effective strategies in improving students' mathematical communication skills. This research is a qualitative descriptive study which was conducted on April 16, 2022. The subjects of this study consisted of 13 teachers who taught mathematics in the West Bogor area. The subject-taking technique in this study used a Purposive Sampling Technique. Based on the results of this study, effective strategies in improving students' mathematical communication skills can be carried out in various ways, namely by using student-centered learning models, diverse learning methods, comfortable and pleasant classroom atmosphere, providing positive feedback, ways of asking questions by asking questions. using lighter questions, language that is easy to understand and relates to applications in everyday life.